Thermal catalytic decomposition of methane over unreduced Ni/SiO2 and Ni/Al2O3 catalysts. - ílvaro Calafat ílvaro Calafat; José Aldana, José Aldana; Nora Sánchez, Nora Sánchez (Rev. Téc. Fac. Ing. Univ. Zulia, 2013)
The thermo catalytic decomposition (TCD) of methane at 823-973 K was investigated over unreduced 30 wt% Ni/Al2O3 and Ni/SiO2 catalysts. The catalytic activities of the unreduced catalysts were compared with those obtained for the catalysts pre-reduced with H2. Methane decomposition was studied by the thermogravimetric method, monitoring the mass change of the catalyst due to carbon de- position. The initial specific rates of carbon formation (rc,i), and as a consequence the catalyst activity, on the unreduced catalysts were higher than those for the pre-reduced catalyst. The differences observed seemed not to be related to the particle size of the nickel species, determined from X-raydiffraction analysis (XRD). Arrhenius plots of the initial rates indicated that the rate-determining step for carbon formation is independent of whether the catalysts are pre-reduced or not. Differences in catalytic activity between unreduced and pre-reduced catalysts are probably due to heat coupling effects during the reduction of NiO by CH4, H2 and deposited carbon at the beginning of the decomposition of methane.